10m+6=6m+30

Simple and best practice solution for 10m+6=6m+30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10m+6=6m+30 equation:


Simplifying
10m + 6 = 6m + 30

Reorder the terms:
6 + 10m = 6m + 30

Reorder the terms:
6 + 10m = 30 + 6m

Solving
6 + 10m = 30 + 6m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-6m' to each side of the equation.
6 + 10m + -6m = 30 + 6m + -6m

Combine like terms: 10m + -6m = 4m
6 + 4m = 30 + 6m + -6m

Combine like terms: 6m + -6m = 0
6 + 4m = 30 + 0
6 + 4m = 30

Add '-6' to each side of the equation.
6 + -6 + 4m = 30 + -6

Combine like terms: 6 + -6 = 0
0 + 4m = 30 + -6
4m = 30 + -6

Combine like terms: 30 + -6 = 24
4m = 24

Divide each side by '4'.
m = 6

Simplifying
m = 6

See similar equations:

| x-15=x/77 | | -4p-12=12 | | w+2.9=6.4 | | z^2=-2z-14 | | -3/8t=1/6 | | y=20-3(1) | | g=y-cx | | 8(3n+3)=8(6n+3)+2 | | 3(1.5x+9)= | | 2(3x-2)=3(4x+5)+7X | | 144x=3268.80 | | 5x-12+x=-13 | | 4/3x3.14x3.04^3 | | -4p+8(p+3)=4(p-8)+2 | | 6(x+4)-3x=11 | | f(2.5)=2x^2-3+7 | | (4x-15)+(5x+11)+(5x+5)+(6x+19)=360 | | -6.5-4x-1.6-3x=-6+9.8 | | 7(x^2)-2=5x | | 8xt=32 | | 2(5x+4)-2(9x+2)= | | 7n-(1+7n)=3(n-7)-7n | | 72x(3/2)n | | 30x^2-114x+108=0 | | n+9=25 | | 19h+1.50=15+2.75 | | (X-5)/4=-20 | | 3(w-2)-2=8-(w+4) | | 9x=12+60 | | 2450=1500+z | | 19h+1.50=15+2.75h | | -42/21 |

Equations solver categories